Pelatihan Penggunaan E-Commerce Shopee dan Sosial Media sebagai Alat Pemasaran Produk - Moch. Faizul Huda; Yunus Febriyansah; Maulida Dini Karimah; Meliya Ayu Romantika; Alifiyah Alqaedah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2024)
Digital marketing is a marketing strategy to promote a business, brand or business by utilizing digital media. Through digital-based media, businesses gain access to resources that are otherwise unavailable to business owners, including the people living in Seketi Village, Jombang. One of the community groups in Seketi Village which operates in the business sector is the Asman Group. Implementation of service activities carried out by the team of University of KH. A. Wahab Hasbullah is product marketing training and community business improvement. This training activity uses a face-to-face/offline meeting method between resource persons and partners located at the Seketi Village Hall office, Mojoagung District, Jombang Regency. The implementation of this service program in the form of